Cross Talk Between TGF-β and JAK Expressions and Nepherotoxicity Induced by Tetrachloromethane: Role of Phytotherapy - Laila M. Fadda; Ahlam M. Alhusaini; Hanaa M. Ali; Iman H. Hasan; Amira M. Badr; Enas A. Zakaria (SAGE Publishing, 2019)
The aim of the current study is to assess the effectiveness of milk thistle seeds (Mth) in combination with Taraxacum officinale ( Tof ) and/or Camellia sinensis ( Csin ) against tetrachloromethane (Tcm) renotoxicity in rats. Tetrachloromethane was injected in a single dose, followed by 1-month treatments with Mth, Tof , and Csin alone or in combination. Serum urea, uric acid, and creatinine levels were significantly increased matched with the control group. Masson trichrome stain revealed increase in the deposition of fibrous tissue in the interstitium between the tubules and the renal corpuscles. Immunohistochemical analysis of kidney tissues revealed that Tcm induced an increase in the immune response of tumor growth factor β (TGF-β) and Janus kinase (JAK) protein expressions and cysteine-aspartic acid protease 3 (caspase 3), while B-cell lymphoma 2 (Bcl2) was downregulated. Treatment with the antioxidants in question either alone or in combination ameliorated all kidney function parameters and showed mild immune reactivity toward TGF-β and JAK protein expressions in blood vessels and glomeruli in the kidney tissues and downregulated caspase 3 and activated Bcl2 protein expression. The combination regimen of the 3 antioxidants showed the most significant renoprotective effect. This was also confirmed histopathologically. It was concluded that the antioxidant mixture is considered as a promising candidate toward renal dysfunction and immune reactivity induced by Tcm and other toxicants.